Frequency and Etiology of ADHD in New Onset Epilepsy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2007)
The prevalence, complications and etiology of ADHD were determined in 75 children (age 8-18 years) with new/recent onset idiopathic epilepsy nd 62 healthy first-degree cousin controls, in a study at University of Wisconsin School of Medicine and Public Health, Madison, WI; and Rosalind Franklin University of Medicine and Science, North Chicago, IL.